2012
DOI: 10.1080/13607863.2012.678482
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ relationship closeness with the person with dementia predicts both positive and negative outcomes for caregivers’ physical health and psychological well-being

Abstract: Closer relationships between caregivers and care recipients with dementia are associated with positive outcomes for care recipients, but it is unclear if closeness is a risk or protective factor for the health and psychological well-being of caregivers. We examined 234 care dyads from the population-based Cache County Dementia Progression Study. Caregivers included spouses (49%) and adult offspring (51%). Care recipients mostly had dementia of the Alzheimer’s type (62%). Linear mixed models tested associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 51 publications
(70 reference statements)
11
117
0
9
Order By: Relevance
“…Meta-analyses of research have concluded that weak emotional ties between caregiver and care recipient were associated with higher levels of caregiver depression (Quinn, Clare, & Woods, 2009). Similar findings reported by Fauth et al (2012) showed that higher levels of closeness between the caregiver and care recipient were significantly associated with less depression and better mental health ratings in caregiver outcomes. Furthermore, research suggests that it is the deterioration of the interpersonal relationship, as perceived by the caregiver, which contributes to heightened caregiver burden and ultimately more depressive symptoms (Adams, McClendon, & Smyth, 2008).…”
Section: Introductionsupporting
confidence: 89%
“…Meta-analyses of research have concluded that weak emotional ties between caregiver and care recipient were associated with higher levels of caregiver depression (Quinn, Clare, & Woods, 2009). Similar findings reported by Fauth et al (2012) showed that higher levels of closeness between the caregiver and care recipient were significantly associated with less depression and better mental health ratings in caregiver outcomes. Furthermore, research suggests that it is the deterioration of the interpersonal relationship, as perceived by the caregiver, which contributes to heightened caregiver burden and ultimately more depressive symptoms (Adams, McClendon, & Smyth, 2008).…”
Section: Introductionsupporting
confidence: 89%
“…Previous studies referred to in this paper (Collins & Swartz, 2011; The National Board of Health and Welfare 2012a; The National Alliance for Caregiving, 2009;Andrén & Elmståhl, 2005;Andrén & Elmståhl, 2008a;Bruvik, Ulstein, Hylen Ranhoff, & Engedal, 2012;Roth, Perkins, Wadley, Temple, & Haley, 2009;Roth et al, 2013;Pinguart andSörensen, 2011 Lautenschlager et al, 2012;van der Lee, Bakker, Duivenvoorden, & Dröes, 2014;Ekwall, Sivberg, Rahm, & Hallberg, 2006;Buyck et al, 2011;Broe et al,1999;Schultz & Sherwood, 2008;Fauth et al, 2012;Iecovich, 2011) have given us some answers. In this study we aim to broaden the knowledge on this topic by discussing how perceived strain affects informal caregivers' health-related quality of life (HRQoL) and life satisfaction (LS).…”
Section: Introductionmentioning
confidence: 78%
“…Schultz and Sherwood (2008) state that depression is common and has a negative effect on the caregiver, especially among spouses caring for a person with dementia, and that caregiving often results in chronic stress. Fauth et al (2012) studied the caregivers' relationship closeness with the person with dementia before and after the onset of the disease, and its consequences for caregivers' psychological and physical well-being. They found that higher closeness before the onset of dementia was associated with higher SF12-MCS but also a worsening in the SF12-MCS over time, indicating that closeness has both positive and negative consequences for the caregiver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They did, however, find that increased behavioural disturbances in the person with dementia were associated with a higher degree of conflict and criticism and lower levels of warmth in the relationship. Fauth et al (2012) evaluated the impact of 'closeness' in relationship, as rated by the carer, finding that higher ratings of closeness predicted better mental health and lower depression in the carer.…”
Section: Introductionmentioning
confidence: 99%